Effectiveness Transformational Leadership, Compensation, Innovative Work Behavior on Employee Performance - Ayu Akhmala; Sumartik Sumartik; Dewi Andriani (Universitas Negeri Padang, 2024)
Employees play an important role in the company, especially in operational processes and activities. The purpose of this study is to be able to test the effectiveness of transformational leadership, compensation, innovative work behavior on employee performance. The location of this research was conducted at CV. Gembira Abadi Jaya. The total population of this study were all employees of CV. Gembira Abadi Jaya which amounted to 43 respondents. In this study, the non-probability sample method and saturated sample were used, with a total sample equivalent to the population as a whole. The data collection technique used a questionnaire. The data analysis technique used in this research is Structural Equation Modeling with the Partial Least Squares method. The results of this study indicate that transformational leadership has a significant effect, while compensation has no significant effect and innovative work behavior has a significant effect on employee performance.